Mobile Applications Quick Response Reports For Successful Practices In Computer Laboratory - Ari Amir Alkodri; Supardi Supardi; Burham Isnanto; Seno Hadi Saputro; Agus Dendi Rachmatsyah; Gita Aditia (Institut Teknologi dan Bisnis Bina Sarana Global, 2021)
With the rapid advancement of information technology today, every world of education requires campuses to develop teaching and learning services in their special practicum in the laboratory. Rapid response laboratory services are a form of participation to take part in the implementation of practicum adjusting standard operating procedures (SOP). In this case, the author takes a case study at the Atma Luhur ISB computer laboratory, making a damage report or PC troubleshooting now still in the form of LOG books and manuals, and the processing time is waiting for lecture hours to finish. Thus, a rapid response application process for response and information service laboratories is needed to make it easier for laboratory workers to carry out job descriptions. The method used in designing this rapid response system application is the waterfall model and is run on the Android operating system. The results of the rapid response application in the Atma Luhur ISB laboratory can help smooth practicum in this laboratory, making it easier for the laboratory and to obtain service responses and practicum services more quickly and effectively. This application after being tested for functional aspects by distributing questionnaires to laboratory assistants got an average value of 87.083% (good criteria), so overall it can be concluded that this application can be applied in the Atma Luhur ISB laboratory.